Quantifying the Coordination of Energy Development and Environmental Protection: A Case Study of China. (December 2016) - Zhao, Fang; Zhang, Wenqiang; Wang, Yetang
Abstract: Today, balancing energy development with the desire to protect the environment remains a challenge in the world, especially in developing countries such as China. To make public policy for the balancing of alternative futures, quantification of the coordination between energy development and environmental protection is required. To achieve this end, we firstly establish the index system of energy-environment comprehensive development. Then we calculate the coordination degree of energy development and environment protection by means of principal component analysis and membership function of fuzzy mathematics. The resulting coordination of energy and environment systems in China during 2000-2012 is low with an average coordination degree of 0.6301. In 5 years, energy and environment systems are in the status of incoordination to different extents. To further improve the coordinated status, based on phenomenon analyses and economic theoretical interpretation on the reasons behind, some helpful policies are suggested, including establishment of a policy guarantee system for a coordinated development, implementation of energy green insurance and standardization of new energy market etc..